Simulacra in mobile legends: (Analysis of Jean P. Baudrillard’s theory) - Ari Rizal Faturohman (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP) Sekolah Tinggi Ilmu Agama Buddha Smaratungga, 2022)
The current era of online games is very admired, especially among teenagers. This phenomenon is due to the sophistication of technology as a fruit of human thought, one of which humans managed to create a Mobile Legends Online game. This paper will describe the research results with the theme of Mobile Legends analysis of Simulacra by Jean P. Baudrillard. The method used in this study is a descriptive-analytic method using a literature study on related sources. The author uses the theoretical basis of Jean P Baudrillard’s theory about simulacra and hyperreality. The results obtained from this study indicate that the Mobile Legends is the result of human simulation. The conclusion is that the game and all elements resulting from human visualization of reality will impact the player as described by Jean P. Baudrillard, such as simulation, implosion, subject’s death, loss of binary opposition, and death of reality.